Models of evaluation of educational centers in Europe. Inspiration for a rethinking of the spanish model - Vázquez-Cano, Esteban (Avances en Supervisión Educativa, 2023)
This article presents a comparative analysis of different models of school evaluation in different European countries. Derived from this analysis, the main strengths are identified so that they can serve as inspiration for the rethinking of the Spanish model of school evaluation. Subsequently, a series of dimensions and items are proposed to consider when redesigning the Spanish model. Finally, we propose and discuss the design of a tripartite model of influence in which external evaluation, self-evaluation, training, assessment and dissemination of the results obtained interact in such a way that bureaucracy is minimized, a stable evaluation development schedule is systematized, and the transfer, accountability and generation of knowledge derived from the whole evaluation process is enhanced.
Keywords: school evaluation; transfer; dissemination; accountability; educational improvement